The Effectiveness of the Performance of Supervisors in Tsanawiyah Madrasah (Islamic Junior High School) in Improving the Implementation of the Duties of the Head of the State Tsanawiyah Madrasah (Mtsn) in the Province of Jambi - Abd. Rahman; Ahmad Syuki; Kasful Anwar Us (International Journal of Educational and Life Sciences, 2023)
Based on the researcher's grand tour of Tsanawiyah Madrasahs in the province of Jambi, it was found that firstly, the supervisor's program does not align with the madrasah's needs. Secondly, supervision is only fulfilling obligations without going beyond. Thirdly, the organization of time, work tools, and facilities are not yet optimal. This qualitative research employs a qualitative case approach. The subjects of this study are supervisors of Madrasahs Tsanawiyah, representatives from the Ministry of Religious Affairs Regional Office, and the Head of the Madrasah. Data collection involves observation, interviews, and documentation techniques. Data analysis utilizes the Miles and Huberman model, comprising data reduction, data display, and data conclusion. The research results indicate that the performance of Tsanawiyah Madrasah supervisors in the supervision process in the province of Jambi includes: a) Developing a supervision work program for each semester and each year for the madrasahs under their guidance, b) Providing guidance and assistance to the madrasah head regarding managerial processes, and c) Conducting assessments and monitoring the implementation of education in the supervised Madrasah Tsanawiyah, offering advice and considerations to the madrasah on addressing educational implementation-related issues.